Methodology Based On The Rules Of International Educational Programs In Assessing The Knowledge And Skills Of Primary Class Students - Onakhon Jabborova; Dinorakhon Saparbayeva (Euro Asian Journal Publishing, 2024)
The article analyzes the factors of the methodology based on the voids of international educational programs in assessing the knowledge and skills of primary school students and presents the author's approaches.
Keywords: Primary education; learner and teacher; knowledge and skills